2023
DOI: 10.2147/cia.s410239
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Three Tools for Estimating the Risk of Primary Osteoporosis in an Elderly Male Population in Beijing

Abstract: Purpose This cross-sectional study estimated three clinical tools including the Osteoporosis Self-Assessment Tool for Asians (OSTA), Body Mass Index (BMI), and Beijing Friendship Hospital Osteoporosis Self-assessment Tool for Elderly Male (BFH-OSTM) for identifying primary osteoporosis and found optimal cut-off values in an elderly Han Beijing male population. Materials and Methods We conducted a cross-sectional study, enrolling 400 community-dwelling elderly Han Beijin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, studies have shown that most older men with pre-existing fragility fractures do not know to take screening bone mineral density (BMD) tests or receive treatment [ 13 ]. Therefore, a convenient, simple and highly controllable screening method for men is needed to reflect the risk of osteoporosis in the body and provide a preventive basis for the prevention of osteoporosis in men [ 14 ]. The International Osteoporosis Foundation (IOF) offers a 1-min osteoporosis risk test, a simple and sensitive primary screening tool [ 15 ].…”
Section: Introductionsmentioning
confidence: 99%
“…In addition, studies have shown that most older men with pre-existing fragility fractures do not know to take screening bone mineral density (BMD) tests or receive treatment [ 13 ]. Therefore, a convenient, simple and highly controllable screening method for men is needed to reflect the risk of osteoporosis in the body and provide a preventive basis for the prevention of osteoporosis in men [ 14 ]. The International Osteoporosis Foundation (IOF) offers a 1-min osteoporosis risk test, a simple and sensitive primary screening tool [ 15 ].…”
Section: Introductionsmentioning
confidence: 99%